Human Resource Planning In The Art Exhibition Committee (Case Study: SODALIS Art Exhibition of 2023 Arts Management Students) - Agustina Magdalena (Jurnal Indonesia Sosial Sains, 2025)
Human Resource (HR) planning is essential in organizing events, including art exhibitions, to ensure smooth operations and alignment with organizational goals. It is crucial for both logistical tasks and fostering creativity and collaboration within the committee for a successful exhibition. This research aims to explore how HR planning is applied in the committee of the SODALIS Art Exhibition, organized by the 2023 Arts Management students. The research specifically examines how HR planning supports the exhibition's success in managing human resources effectively and achieving the exhibition's goals. The study uses a qualitative approach, utilizing participatory observation and documentation analysis. The researcher, who was involved as both the chairperson and a committee member, observed and documented the exhibition's planning and execution from its initial committee formation to its conclusion. The researcher also compared theoretical HR planning models with the actual practices observed during the exhibition. The HR planning process in the SODALIS Art Exhibition successfully met the human resource needs, organized committee members effectively, and ensured smooth coordination among them. The tasks were distributed efficiently, which helped in avoiding unnecessary resource allocation and operational costs. The planning process contributed to the development of a collaborative committee culture, fostering creativity and innovation, and achieving a successful event. HR planning is essential in organizing an art exhibition, ensuring that human resources are utilized efficiently to meet organizational goals. The study highlights the importance of proper HR planning in achieving the success of such events, demonstrating that a well-structured committee can optimize resources, improve efficiency, and enhance the overall outcome of the exhibition. This research provides valuable insights for future art exhibitions and other events requiring effective HR planning.